2019
DOI: 10.4094/chnr.2019.25.2.184
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Parental Stress and Nurses' Communication as Perceived by Parents of High-risk Newborns

Abstract: This study aimed to characterize the relationship between parental stress and nurses' communication as perceived by parents of high-risk newborns in a neonatal intensive care unit (NICU). Methods: The participants were 54 parents of high-risk newborns in a NICU. Data were collected from January to March 2018. Parental stress and parents' perceptions of nurses' communication ability and styles were measured using a questionnaire. Results: The average scores for parental stress and nurses' communication ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
2
11
2
Order By: Relevance
“…In this study, the mean score for nurses' non-verbal communication ability was higher than the mean score for nurse's verbal communication ability. This result is similar to that of a study by Lee et al [24] concerning the parents of high-risk newborns. However, a study by Kim [8] on adult inpatients found that the mean score for nurses' verbal communication ability was higher than the mean score for nurses' non-verbal communication ability.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the mean score for nurses' non-verbal communication ability was higher than the mean score for nurse's verbal communication ability. This result is similar to that of a study by Lee et al [24] concerning the parents of high-risk newborns. However, a study by Kim [8] on adult inpatients found that the mean score for nurses' verbal communication ability was higher than the mean score for nurses' non-verbal communication ability.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the mean score for the communication ability of nurses perceived by the mothers (mean=4.59, with a possible score range of 1-5) was higher than that of a study by Lee et al [24] (mean=4.38) in which the communication ability of nurses perceived by parents of high-risk newborns was measured using the same tool. This difference may be because, in the study by Lee et al [24], communication between nurses and parents of high-risk newborns took place in the context of limited visiting hours in a neonatal intensive care unit. However, in this study, communication between nurses and mothers of hospitalized children occurred in a pediatric ward that presented relatively more opportunities for regular communication.…”
Section: Discussioncontrasting
confidence: 78%
“…Chemical transformations of both renewable and non‐renewable resources to products of greater value, such as methane to methanol, or biomass polymers to simple sugars, represent one of the current challenges in catalysis . Both of these transformations occur in nature with the help of copper‐containing enzymes.…”
Section: Figurementioning
confidence: 99%
“…While an integrative review indicated the necessity of tailored interventions for South Korean mothers [21], our qualitative study lays the groundwork for the development and refinement of family interventions in the South Korean context. Thus, mothers of high-risk infants can cope more effectively with stress when their opinions are recognized by medical staff [22] in a friendly environment [23]. As family advocates, healthcare providers should make efforts to design favorable environments and provide support to families by addressing and accommodating their changeable needs within the complexity of their NICU experiences [24,25].…”
Section: Introductionmentioning
confidence: 99%